Facebook marketing for dummies - Dunay, Paul (Wiley, 2011)
Recruit fans and turn them into customers! This book makes it easy to create a page, add applications to it, host an event, and much more. It's an easy-to-follow blueprint for marketing and promoting your organization on Facebook!